Geographical prevalence of dens invaginatus in the upper lateral teeth of young adult Turkish men - Elif Aybala Oktay; Serpil Karaoğlanoğlu; Numan Aydın; Akın Alper; Bilge Ersöz (Gülhane Tıp Dergisi, 2022)

(untitled)
Aims:Dens invaginatus, a malformation of teeth caused by infolding of the dental papilla during development or invagination of layers of the enamel organ in dental papillae. Its aetiology is unclear. The present study was conducted to investigate the characteristics of the patients with dens invaginatus anomaly.Methods:A single-center, cross-sectional, retrospective study was conducted on male subjects aged 18 to 24 years. Dens invaginatus in maxillary lateral incisors were identified using periapical radiographs. The evaluation was performed on patients with and without abnormalities.Results:A total of 316 records were evaluated and 296 individuals were eligible for the analysis. No abnormality was detected in 210 (70.9%) individuals, whereas 86 individuals (29.1%) had images of dens invaginatus. The abnormalities were bilateral in 59 (19.9%) and unilateral in 27 (9.1%) individuals. Among the 59 individuals with bilateral dens invaginatus, most subjects were from the Marmara region (27.1%). Unilateral dens invaginatus was most frequently detected in the Marmara, Black Sea, and Eastern Anatolia regions.Conclusions:This study showed that up to one-third of young adult males had images of dens invaginatus on an untargeted screening. The prevalence of dens invaginatus varied across different geographical regions of Turkey.